The efficacy of psychiatric nursing process in alcohol and drug dependency treatment - Sağkal, Tülay; Gürkan, Ayça (Journal of Dependence, 2008)
Achieving of positive conclusions in alcohol and drug dependence treatment is being made with the supplementary and complementary methods. One of the team members is a psychiatric nurse who takes part a role in the supplementary and complementary treatment. Psychiatric nurse should use the nursing process consists of assessment, nursing diagnosis, outcome, planning, intervention and evaluation that gains professional one identify for her profession in treatment of dependence. The using of psychiatric nursing process in alcohol and drug dependency treatment is important due to care quality service on patients. Therefore, the nursing process that is a problem-solving method should be applied in the psychiatric clinical and it should be provided ongoing nursing care.